Artemis Fowl. [2], The Arctic incident : the graphic novel - Colfer, Eoin; Donkin, Andrew; Rigano, Giovanni; Lamanna, Paolo (New York : Disney/Hyperion Books, 2009)
At the start of his second adventure, Artemis is at boarding school in Ireland when he receives an urgent video e-mail from Russia. In it is a plea from a man who has been kidnapped by the Russian Mafiya--a man Artemis had thought he would never see again: his beloved father. As Artemis rushes to his rescue, he is joined by Captain Holly Short of the LEPrecon fairy police. This time Artemis will join forces with the fairies if he wants to save one of the few people in the workd he loves.
Keywords: Fairies -- Fiction; Kidnapping -- Fiction; Magic -- Fiction; Mothers and sons -- Fiction; Fowl, Artemis (Fictitious character) -- Fiction; England -- Fiction; Great Britain -- Fiction; Comic books, strips, etc; Fantasy comic books; Graphic novels; Young adult fiction